2016
DOI: 10.1002/chem.201600913
|View full text |Cite
|
Sign up to set email alerts
|

Tetrazine Assists Reduction of Water by Phosphines: Application in the Mitsunobu Reaction

Abstract: Reaction of 3,6-disubstituted-1,2,4,5-tetrazines with water and PEt forms the corresponding 1,4-dihydrotetrazine and OPEt . Thus PEt , as a stoichiometric reductant, reduces water, and the resulting two reducing equivalents serve to doubly hydrogenate the tetrazine. A variety of possible initial interactions between electron-deficient tetrazine and electron-rich PR , including a charge transfer complex, were evaluated by density functional calculations which revealed that the energy of all these make them spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
(74 reference statements)
0
21
0
1
Order By: Relevance
“…Despite enormous efforts made over the last century, the direct use of water as a hydrogen donor in organic synthesis remains a challenging and unsolved task. According to the known data, the splitting of water can follow the following three pathways: 1) oxidative splitting generating O 2 ; 2) reductive splitting generating H 2 ; 3) direct splitting into elements (O 2 +H 2 ) . Most of the presently known strategies of water splitting are photocatalytic or photoelectrochemical processes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite enormous efforts made over the last century, the direct use of water as a hydrogen donor in organic synthesis remains a challenging and unsolved task. According to the known data, the splitting of water can follow the following three pathways: 1) oxidative splitting generating O 2 ; 2) reductive splitting generating H 2 ; 3) direct splitting into elements (O 2 +H 2 ) . Most of the presently known strategies of water splitting are photocatalytic or photoelectrochemical processes .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the development of novel reductive water splittings used in catalytic hydrogenations remains one of the “holy grails” of modern organic synthesis. In this connection, the research made within the last few years indicates that reductive water splitting can be initiated by various diboron compounds, phosphines, DMF/Cu system, iron powder, SmI 2 , and Ti III complexes…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, zinc pincer complexes have recently shown promise for metal‐ligand cooperation to promote catalytic hydrogenation, [16] as well as an H 4 Zn pincer complex catalyzing the dehydrogenation of alcohols [17] . We have previously shown the ability of tetrazines to assist in the reduction of water by phosphines, where H 4 btzp is quantitatively generated [18] . We have now found that a conversion of tetrazine to dihydrotetrazine can be accomplished simply with H 2 as the reductant, using catalytic Pd/C, which alleviates the need for removal of phosphine oxides.…”
Section: Resultsmentioning
confidence: 99%
“…Figure compares the 1 H NMR spectra of relevant complexes together with those of btzp Et and H 4 btzp Et , the latter showing the effect on 1 H NMR of tetrazine reduction (hydrogenation). If reduction is occurring at the tetrazine ring in M­(btzp) 2 , the CH 2 1 H NMR chemical shift should be most sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 1). The pattern of single-and double-bond intra-tetrazine distances in the fully reduced (hydrogenated) bis-dihydrotetrazinyl pincer 13 serves as a comparison. Scheme 2 shows anticipated bond length changes, upon reduction.…”
Section: +mentioning
confidence: 99%